Efficient Synthesis of (–)-Hanishin, (–)-Longamide B, and (–)-Longamide B Methyl Ester through Piperazinone Formation from 1,2-Cyclic Sulfamidates - Shiokawa, Zenyu; Inuki, Shinsuke; Fukase, Koichi; Fujimoto, Yukari (Synlett, 2016)
We describe a simple chiral-pool synthesis of (–)-longamide B, (–)-longamide B methyl ester, and (–)-hanishin. The key feature of the total synthesis is the formation of a piperazinone from a 1,2-cyclic sulfamidate and methyl 2-pyrrolecarboxylate, which permits efficient construction of the pyrrolopiperazinone core scaffold.
Keywords: heterocycles; hanishin; longamide B; asymmetric synthesis; piperazinones; sulfamidates